Smells Like Home: Chemically Mediated Co-Habitation of Two Termite Species in a Single Nest - Jirošová, Anna; Sillam-Dussès, David; Kyjaková, Pavlína; Kalinová, Blanka; Dolejšová, Klára; Jančařík, Andrej; Majer, Pavel; Cristaldo, Paulo Fellipe; Hanus, Robert (Journal of chemical ecology, 2016)
Termite nests often are referred to as the most elaborate constructions of animals. However, some termite species do not build a nest at all and instead found colonies inside the nests of other termites. Since these so-called inquilines do not need to be in direct contact with the host population, the two colonies usually live in separate parts of the nest. Adaptations of both the inquiline and its host are likely to occur to maintain the spatial exclusion and reduce the costs of potential conflicts. Among them, mutual avoidance, based on chemical cues, is expected. We investigated chemical aspects of cohabitation between Constrictotermes cavifrons (Nasutitermitinae) and its obligatory inquiline Inquilinitermes inquilinus (Termitinae). Inquiline soldiers produce in their frontal glands a blend of wax esters, consisting of the C12 alcohols (3Z)-dodec enol, (3Z,6Z)-dodecadienol, and dodecanol, esterified with different fatty acids. The C12 alcohols appear to be cleaved gradually from the wax esters, and they occur in the frontal gland, in soldier headspace, and in the walls of the inquiline part of the nest. Electrophysiological experiments revealed that (3Z)-dodecenol and (3Z,6Z)-dodecadienol are perceived by workers of both species. Bioassays indicated that inquiline soldier heads, as well as the two synthetic compounds, are attractive to conspecific workers and elicit an arresting behavior, while host soldiers and workers avoid these chemicals at biologically relevant amounts. These observations support the hypothesis that chemically mediated spatial separation of the host and the inquiline is an element of a conflict-avoidance strategy in these species.
Keywords: vosky; Smell; Alcohols; komunikace zvířat; feromony; Nesting Behavior; úniková reakce; Waxes; Isoptera; zvířata; Escape Reaction; Esterification; čich; Pheromones; Esters; hnízdění; Animal Communication; Animals; alkoholy; esterifikace; estery